Vonis Game Development to Improve Physical Education Learning Skills at Elementary School - Enno Malik Ibrahim; Hananto Tyas Saputro (Universitas Negeri Semarang, 2026)
The background of the study departs from the finding that learning net games tends to be difficult for students to understand due to its complex techniques and the lack of learning media that are appropriate to the characteristics of elementary school students. This study aims to develop the Vonis game as a physical education learning medium to improve students' learning skills in net games material. This study uses the Research and Development method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The results show that the Vonis game is considered very feasible based on validation by material experts, media experts, and design experts. Staged trials involving 4 students in individual tests, 8 students in small group tests, and 16 students in large group tests showed an increase in student understanding, motivation, and engagement in learning. The analysis shows that the Vonis game is able to simplify the net game pattern through a simple field design, easy rally rules, and a safe plastic ball so that it is appropriate to the abilities of elementary school students. The study concludes that the Vonis game is effective as an alternative learning medium in improving the quality of physical education learning, although this study still has limitations related to the number of subjects and the scope of the trial.